2020
DOI: 10.1126/sciadv.aaz0495
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanocarriers deliver siRNA to intact plant cells for efficient gene knockdown

Abstract: Posttranscriptional gene silencing (PTGS) is a powerful tool to understand and control plant metabolic pathways, which is central to plant biotechnology. PTGS is commonly accomplished through delivery of small interfering RNA (siRNA) into cells. Standard plant siRNA delivery methods (Agrobacterium and viruses) involve coding siRNA into DNA vectors and are only tractable for certain plant species. Here, we develop a nanotube-based platform for direct delivery of siRNA and show high silencing efficiency in intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
141
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 57 publications
1
141
1
Order By: Relevance
“…[ 42 ] Demirer et al suggested that CNTs 250 nm in length enter tobacco ( N. benthamiana ) cells pronouncedly less than CNTs 776 nm in length, reinforcing the idea that only one dimension of the NP needs to be smaller than the size exclusion limit. [ 29 ] Although the authors did not offer an explanation for this observation, we speculate that the longer CNTs have a higher ratio of local rate of strain to rotational diffusivity that encourages flow‐induced alignment to the pores of the cell wall more effectively for penetration of the cell wall, as previously shown for the renal clearance of intravenously injected CNTs. [ 45 ] As a notable exception to the size exclusion limit of the cell wall, Palocci et al showed that PLGA NPs of up to ≈50 nm in diameter are able to penetrate the cell wall and enter intact grapevine cells, citing strong adhesion between the PLGA NPs and the cell wall.…”
Section: Perspectivesmentioning
confidence: 71%
See 3 more Smart Citations
“…[ 42 ] Demirer et al suggested that CNTs 250 nm in length enter tobacco ( N. benthamiana ) cells pronouncedly less than CNTs 776 nm in length, reinforcing the idea that only one dimension of the NP needs to be smaller than the size exclusion limit. [ 29 ] Although the authors did not offer an explanation for this observation, we speculate that the longer CNTs have a higher ratio of local rate of strain to rotational diffusivity that encourages flow‐induced alignment to the pores of the cell wall more effectively for penetration of the cell wall, as previously shown for the renal clearance of intravenously injected CNTs. [ 45 ] As a notable exception to the size exclusion limit of the cell wall, Palocci et al showed that PLGA NPs of up to ≈50 nm in diameter are able to penetrate the cell wall and enter intact grapevine cells, citing strong adhesion between the PLGA NPs and the cell wall.…”
Section: Perspectivesmentioning
confidence: 71%
“…Recent studies on NP‐based gene delivery predominantly involve the use of mature plants (e.g., tobacco ( N. benthamiana )), [ 29,42,43 ] yet few of them describe similar applications to plant suspension cells (e.g., canola ( Brassica napus ) cells [ 57 ] ). Note that these two types of plant systems (mature plants vs plant cells) may serve different objectives.…”
Section: Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, single walled carbon nano tubes (CNTs) (∼1–1000 nm) and carbon dots (∼3 nm) can be chemically functionalized to carry genetic material and can diffuse through plant cell walls and deliver cargo to targeted cell organelles ( Figure 2C ). Recently, CNTs and carbon dots have enabled efficient DNA delivery into both nuclear ( Demirer et al, 2019 , 2020 ) and chloroplast genomes to achieve gene silencing ( Kwak et al, 2019 ), without external biolistics or chemicals and with no DNA integration into mature plants. Nano carbons such as CNTs, fullerenes, graphene, and polymeric NPs including polyethyleneimine-coated NPs are promising for biomolecule delivery (DNA/RNA/Proteins and RNPs) into plant cells targeting germline or somatic tissues.…”
Section: Nanoparticles For Delivering Biomolecules To Facilitate Planmentioning
confidence: 99%